Lacustrine groundwater discharge and lake water quality evolution - Yanxin Wang; Yao Du; Yamin Deng; Yiqun Gan; Peifang Wang; Teng Ma; Jianbo Shi; Xianjun Xie (地质科技通报, 2022)
Lake eutrophication is one of the most typical and serious water environmental problems in the world, and input of both point-source and non-point source nutrients into lake has been the focus of previous studies.However, the role of surface water-groundwater interactions in the occurrence and evolution of lake eutrophication has been often neglected.In this paper, the patterns of groundwater-lake water interactions were summarized, the research progress on the influence of groundwater discharge on the hydrology and water quality of lake were reviewed, and the advantages and applicability of different quantifying methods such as seepage meter measurement, water balance, radon mass balance, temperature tracing, and numerical simulation) were compared.The state-of-art of the studies and major challenges in understanding the spatial-temporal variability of groundwater discharge to lakes, and the transport and transformation of nitrogen and phosphorus at the groundwater-lake interface were reviewed.And three directions for the future study in this field were proposed: 1) characterizing the spatial-temporal variability of lacustrine groundwater discharge using multiple methods; 2) accurately quantifying the loads of nitrogen and phosphorus with groundwater discharge into lakes, on the basis of revealing hydrobiogeochemical processes at the interface; and 3) unraveling the effect of strong anthropogenic activities on groundwater-lake interactions.